The tip of the iceberg: Ice as a non-human actor in the climate change debate - Bjørst, Lill (Études/Inuit/Studies, 2010)
AbstractThe global climate change debate has the Arctic as a core region of concern and ice has become a central aspect of discourses. This article discusses ice representations from six different contexts linked to the 2009 United Nations Climate Change Conference (COP15) in Copenhagen. The author argues that even though the discussions often seem to be centred on ice alone, the latter enters into narratives and metaphors that have wider implications for how the Arctic and its Indigenous peoples are represented. Ice becomes a non-human actor, framing the discussions, acting in specific ways, and linking hybrid networks. Indeed it is used in diverse platforms by scientists, politicians, governments, and NGOs, as well as by Inuit hunters and fishers.